Research progress and treatment status of malignant ascites - Jing He; Hui-ping Zhang (Frontiers in Oncology)
Malignant ascites (MA), a common and serious complication of various cancers in the abdominal cavity, originates from the extensive infiltration, metastasis, and growth of cancer cells in or on the abdominal cavity, leading to abnormal accumulation of fluid in the abdominal cavity and the formation of MA. MA seriously reduces the quality of life of cancer patients, shortens their survival period, and generally has a poor prognosis. Modern medicine has developed various strategies for the treatment of MA, including targeted supportive treatment, diuretic treatment, abdominal paracentesis, surgical intervention, and intraperitoneal administration therapy. Among them, chemotherapy, as one of the important treatment methods, includes both systemic chemotherapy and intraperitoneal chemotherapy, especially pressurized intraperitoneal aerosol chemotherapy (PIPAC), hyperthermic intraperitoneal chemotherapy (HIPEC), and foam-based intraperitoneal chemotherapy (FBIC), providing a new choice for the treatment of MA. In addition, innovative treatment methods such as gas-based intra-abdominal hyperthermia (GIH) combined with dehydration therapy have also shown promising application prospects. This article delves into multiple aspects of MA, including its concept, mechanism of occurrence, clinical manifestations, differential diagnostic methods, and current treatment status and research progress. This comprehensive review aims to provide valuable references for effectively controlling MA, improving cancer patients’ quality of life, and prolonging the survival cycle of cancer patients in clinical practice. Malignant ascites (MA) is a common complication of cancer, which originates from the extensive infiltration, metastasis, and growth of cancer cells in the abdominal cavity or peritoneum, leading to abnormal accumulation of peritoneal fluid. It is a common clinical manifestation in the late stage of cancer. Its symptoms are stubborn and recurrent, which can lead to abdominal pain, bloating, poor appetite, fatigue, breathing difficulties, and even multiple organ failure. The median survival time for cancer patients with MA is generally 5 to 6 months. The prognosis is poor, and it is imperative to seek more active and effective treatment plans. This article reviews the research and treatment status of MA, aiming to provide certain value for controlling MA and improving the quality of life of patients.